Cecal Dieulafoy lesion is a rare cause of lower gastrointestinal bleeding: A case report - Bibek Saha; Divya Takkellapati; Thomas J. Beckman (SAGE Open Medical Case Reports, 2023)
Dieulafoy lesions are a rare but life-threatening cause of gastrointestinal bleeding. Colonic Dieulafoy lesions are exceptionally rare, comprising only 2% of these lesions. We present a case of cecal Dieulafoy lesion as an unusual cause of lower gastrointestinal bleeding—along with hemoptysis. An 81-year-old male with pulmonary hypertension presented with a one-day history of hematochezia. He subsequently developed new small-volume hemoptysis/hematemesis with increasing oxygen requirements. Bronchoscopy revealed old blood in the left lower lobe, with no active bleeding. The hemoptysis was attributed to severe pulmonary hypertension. Colonoscopy revealed a 2-mm cecal Dieulafoy lesion with spurting bleeding, which was clipped. We report a rare case of cecal Dieulafoy lesion with only 13 other published cases. Our case was complicated by hemoptysis creating an interesting diagnostic dilemma. In patients bleeding from both oral and anal orifices, a brisk upper gastrointestinal bleed—as well as independent causes involving the gastrointestinal and respiratory tracts—should be considered.